RESEARCH ON STRESS FATIGUE OF TWIN SCREW COMPRESSOR ROTOR BASED ON THERMAL ANALYSIS - WANG JunLi; LU ZhengWu; LI QingQing; LI TuoLei; LEI Shuai; FENG MingHao (Jixie qiangdu)
In view of the temperature field generated during the working process of the twin-screw compressor,the rotor produces thermal deformation and thermal stress,which is likely to cause fatigue damage to the rotor. Therefore,it is of great significance to analyze the stress fatigue of the screw rotor under the action of temperature load. Based on the finite volume method to numerically simulate the temperature field of the compressor in the working process,the GGI（ General Grid Interface）interpolation technology was used to transfer the temperature load to the rotor structure grid,and a thermo-solid unidirectional coupling simulation method based on loose coupling was established. The accuracy of the method was verified by using " L-shaped large diameter buried pipeline ". By solving the static balance equation of the rotor structure,the deformation and stress distribution of the rotor under the action of temperature load were studied. Finally,the fatigue life of the rotor was analyzed through the revised stress fatigue S-N curve. The research results show that the maximum deformation of the screw rotor occurs at the end where the male rotor is connected to the motor. The tooth tip of the female rotor and the tooth root of the male rotor produce a large stress concentration,and with the increase of temperature,the service life of the screw rotor Gradually decreases.This method can provide reference for compressor design research and optimization upgrade.